New 'Agrodok' on field surveying - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1991)
CTA has financed the translation into English of another in the low-cost series of Agrodok booklets produced by Agromisa in The Netherlands. Field surveying for land and water management gives basic information on how to measure fields and stake...